Volume as a Mediating in the Effect of Costs on Net Profit - Andriansyah Komarudin (International Journal of Scientific Multidisciplinary Research, 2024)
This research aims to determine the effect of promotional costs and production costs on net profit, with sales volume as a mediating variable. The data source uses secondary data with a quantitative research method. The sample was taken using purposive sampling techniques based on specific criteria, resulting in the annual financial reports of 13 companies in the food processing subsector for the period of 2020-2022. The data analysis method was conducted using path analysis models, with testing carried out through panel data regression, correlation analysis, determination coefficient analysis, hypothesis testing using t-tests and F-tests, and the bootstrap method. The analysis results show that both promotion costs and production costs have a low correlation with net profit, while the contribution of promotion costs, production costs, and sales volume to net profit is very strong when considered together. In the relationship between promotion costs and net profit, sales volume mediates the indirect relationship; whereas in the relationship between production costs and net profit, there is no mediation